Model Kebijakan Moneter Islam dalam Menghadapi Krisis Ekonomi - Amirullah, Sir Haykal Alam; Yazid, Muhammad (Jurnal Keislaman, 2025)
This study aims to determine various Islamic monetary policies that can be used to deal with economic crises such as monetary crises and inflation. Monetary policy is a policy carried out by the central bank in this case is BI (Bank Indonesia) to regulate the amount of money in circulation and interest rates. However in the Islamic perspective,  the interest rate is a form of usury, so in the Islamic perspective the interest rate is changed to zakat of 2.5%. Through the library research methodology, researchers collect data from previous journals and several books to find out what models can be done by Islamic monetary policy in dealing with economic crises. The results of the study show Islamic monetary policy models that can be used to deal with economic crises such as 1) Reserve Ratio, 2) Moral Suassion, 3) Lending Ratio, 4) Refinance Ratio, 5) Profit Sharing Ratio, 6) Islamic Sukuk, 7) Government Investment Certificate, and 8) Sharia mutual funds. This study provides an understanding of various models of Islamic monetary policy to avoid usury to overcome economic crises. And this proves that sharia-based monetary policy can compete in modern times today.